The Migrant Health Gap and the Role of Labour Market Status: Evidence from Switzerland - Sara Rellstab; Marco Pecoraro; Alberto Holly; Philippe Wanner; Karine Renard (University of Neuchâtel, Institute of Economic Research (IRENE), 2016)
With more than a fifth of the population being foreign citizens, Switzerland offers an ideal case to study the migrant health gap and the role of labour market status on the migrants' health. This paper examines the potential health gaps between Swiss nationals and different migrant groups (from the permanent foreign resident population), and how alternative types of labour market status affect health among each selected groups. Using a sample of working-age males from the Swiss Labour Force Survey for the years 2003-2009, we estimate a model with a dichotomic dependent variable and test the potential endogeneity of labour market status. Our empirical strategy avoids inconsistencies incurred by unobserved heterogeneity and simultaneity of the choice of labour market status. We observe a health gap in terms of chronic illness between Swiss nationals and all considered migrant groups. Compared to the Swiss, nationals from former Yugoslavia and Turkey have a worse health status whereas Germans have a lower prevalence of chronic illness. Our findings show a negative influence of part-time work, unemployment, and inactivity on health for all groups under study. Labour market status and standard individual characteristics (human capital, demographic attributes, etc.) explain the health disadvantage for migrants from Italy and Portugal/Spain entirely, whereas it does not for migrants from Turkey and former Yugoslavia. We provide insights on the unconditional health gap between migrants and Swiss nationals and estimate the causal effect of labour market status on chronic illness for different groups of the permanent resident population in Switzerland. The results show a negative correlation between non-employment (i.e. unemployment and inactivity) and health but this effect is reduced when taking into account the endogeneity of this variable. The same conclusion applies when labour market status is subdivided into three types: part-time work, unemployment, and inactivity.
Keywords: 330; Migration; Health; Labour Market; Latent Variable Models; Simultaneous Equation; Panel Data Analysis